Targeting the PI5P4K Lipid Kinase Family in Cancer Using Covalent Inhibitors. Issue 5 (21st May 2020) - Sivakumaren, Sindhu Carmen; Shim, Hyeseok; Zhang, Tinghu; Ferguson, Fleur M.; Lundquist, Mark R.; Browne, Christopher M.; Seo, Hyuk-Soo; Paddock, Marcia N.; Manz, Theresa D.; Jiang, Baishan; Hao, Ming-Feng; Krishnan, Pranav; et al.
Summary: The PI5P4Ks have been demonstrated to be important for cancer cell proliferation and other diseases. However, the therapeutic potential of targeting these kinases is understudied due to a lack of potent, specific small molecules available. Here, we present the discovery and characterization of a pan-PI5P4K inhibitor, THZ-P1-2, that covalently targets cysteines on a disordered loop in PI5P4Kα/β/γ. THZ-P1-2 demonstrates cellular on-target engagement with limited off-targets across the kinome. AML/ALL cell lines were sensitive to THZ-P1-2, consistent with PI5P4K's reported role in leukemogenesis. THZ-P1-2 causes autophagosome clearance defects and upregulation in TFEB nuclear localization and target genes, disrupting autophagy in a covalent-dependent manner and phenocopying the effects of PI5P4K genetic deletion. Our studies demonstrate that PI5P4Ks are tractable targets, with THZ-P1-2 as a useful tool to further interrogate the therapeutic potential of PI5P4K inhibition and inform drug discovery campaigns for these lipid kinases in cancer metabolism and other autophagy-dependent disorders. Graphical Abstract: Highlights: Inhibitor THZ-P1-2 shows PI5P4K enzyme inhibition and target engagement in cells THZ-P1-2 covalently targets unannotated cysteines outside the PI5P4K active site AML/ALL cell lines are broadly sensitive to THZ-P1-2's covalent effects PI5P4K inhibition causes autophagy disruption and upregulates TFEB signaling Abstract : PI5P4K, an understudied kinase family, is essential in various disease contexts. Sivakumaren et al. develop and characterize PI5P4K inhibitor THZ-P1-2, which targets unique cysteines, exhibits effects in biochemical and cellular assays, displays anticancer activity in leukemia cell lines, and causes defects in autophagy similar to PI5P4K gene knockdown or deletion.